Job Satisfaction As A Mediation Mechanism Between Organizational Support And Lecturer Performance - Yuyuk Liana; Bunyamin Bunyamin; Rina Irawati; Benita Rachmania (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study examines how organizational support influences lecturer performance, with job satisfaction positioned as a mediating factor. Lecturer performance is essential for the quality of higher education, yet many lecturers still face challenges such as administrative burdens, limited research facilities, and insufficient organizational support. Using a quantitative approach, the study involved 86 lecturers from higher education institutions in Malang, selected through proportional stratified random sampling. Data were collected through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling. The results indicate that organizational support significantly improves lecturer performance and enhances job satisfaction. Furthermore, job satisfaction has a strong positive effect on lecturer performance and serves as a psychological mechanism that strengthens the relationship between organizational support and performance. These findings demonstrate the importance of supportive organizational practices, including adequate facilities, recognition, and career development opportunities. Higher education institutions are encouraged to prioritize these aspects to foster greater job satisfaction and ultimately improve lecturer performance.